If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14(2f) = 7(f + -2) Remove parenthesis around (2f) 14 * 2f = 7(f + -2) Multiply 14 * 2 28f = 7(f + -2) Reorder the terms: 28f = 7(-2 + f) 28f = (-2 * 7 + f * 7) 28f = (-14 + 7f) Solving 28f = -14 + 7f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-7f' to each side of the equation. 28f + -7f = -14 + 7f + -7f Combine like terms: 28f + -7f = 21f 21f = -14 + 7f + -7f Combine like terms: 7f + -7f = 0 21f = -14 + 0 21f = -14 Divide each side by '21'. f = -0.6666666667 Simplifying f = -0.6666666667
| 9y-(11)-(5y)=-25 | | -53-2i=-I+73 | | y/11=17 | | 6x+4=70 | | 2.4(3.1x+4.9)=75.9+0.87 | | m(m-3)=54 | | 5m-7= | | -4-(1-5)-4x-4= | | x/8=-6 | | 7x+17=3x+1 | | x/8=-7 | | 9y-11-5y=-25 | | 10x^2-2x-6=0 | | -6s+-15=15 | | 3=.33-2b | | 3k^2=-12-20k | | 3a-4a=9-4a | | -4-(1-5)=-4x-4 | | 9+9=97+x | | 9(x+1)-3x=2(3x+1)-4 | | 4(s+1)=12(s+3) | | 18-4x=-36 | | 10x+5(x-3)=15 | | 4e^16x=14 | | 6x-12=2x+36 | | -24y-42=18 | | s+14=17-5s | | 7n^2+2=9n | | 8c+30=10c | | -x-62=136-12x | | 42=7j-28 | | 148-4x=5x*22 |